THE EFFECT OF GREEN PRODUCTS, GREEN PROMOTIONS, GREEN PRICES AND GREEN PLACES ON INTEREST IN BUYING SAVING PRODUCTS OF BANK OCBC NISP (CASE STUDY AT BANK OCBC NISP HEAD OFFICE BRANCH) - Agus Salim; Ade Riyanto Rauf; Markonah, Markonah (Dinasti International Journal of Digital Business Management, 2022)
This study aims to analyze the Influence of Green Products, Green Promotion, Green Prices and Green Places on Interest in Buying Savings Products at Bank OCBC NISP (Case Study at Central Bank OCBC NISP). This study uses primary data and the data used in this study were obtained. from distributing questionnaires to Bank OCBC NISP Customers located at Bank OCBC NISP's head office. The data in this study were processed using the SPSS version 26 application. This study used a sample of 150 respondents who were customers. The results of the study partially show that Green Products, Green Promotions and Green Prices have an influence on consumer buying interest, while Green Places have no influence on buying interest.